2020
DOI: 10.1111/jcmm.15072
|View full text |Cite
|
Sign up to set email alerts
|

A polysaccharide from the dried rhizome of Drynaria fortunei (Kunze) J. Sm. prevents ovariectomized (OVX)‐induced osteoporosis in rats

Abstract: In the present study, a homogenous polysaccharide (DFPW) was isolated and purified from the dried rhizome of Drynaria fortunei, and its protective effect against osteoporosis was investigated in ovariectomized (OVX) rats. Histological analysis indicated that oral administration of DFPW (100 and 400 mg/kg) for 12 weeks significantly improved trabecular bone mass, as demonstrated by the increase in trabecular area, trabecular thickness and its number in OVX rats. Furthermore, the decline of bone mineral density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In modern pharmacological studies of traditional oriental medicines, the polysaccharides of herbal medicines have been confirmed as major bioactive components, which are responsible for various pharmacological activities such as antioxidant, antitumor, anti-hyperglycemic and immune-stimulatory activities [ 32 ]. Especially, several recent studies have demonstrated that bioactive polysaccharides isolated from different plants have potent anti-osteoporotic effects in vivo [ 33 , 34 , 35 ]. In our study, C. myrrha resin-derived polysaccharides (i.e., WCM-PE) markedly inhibited RANKL-induced osteoclastogenesis, which was similar to that of WCM.…”
Section: Discussionmentioning
confidence: 99%
“…In modern pharmacological studies of traditional oriental medicines, the polysaccharides of herbal medicines have been confirmed as major bioactive components, which are responsible for various pharmacological activities such as antioxidant, antitumor, anti-hyperglycemic and immune-stimulatory activities [ 32 ]. Especially, several recent studies have demonstrated that bioactive polysaccharides isolated from different plants have potent anti-osteoporotic effects in vivo [ 33 , 34 , 35 ]. In our study, C. myrrha resin-derived polysaccharides (i.e., WCM-PE) markedly inhibited RANKL-induced osteoclastogenesis, which was similar to that of WCM.…”
Section: Discussionmentioning
confidence: 99%
“…Eucommiae Cortex , rich in polyphenols such as phenolic acids, flavonoids, and lignans, is a kidney-tonifying herbal medicine that has been shown to improve bone histomorphometric parameters in lead-exposed rats. The possible mechanism underlying the effects of Eucommia Cortex extract is the promotion of bone formation by increasing the expression of OPG and the suppression of bone resorption by decreasing the level of RANKL in serum [ 22 ]. Gentiopicroside is the main active ingredient of Gentiana macrophylla Pall., which significantly suppresses RANKL-induced osteoclast formation in bone marrow mesenchymal stem cells (BMMs), with the possible mechanism being the inhibition of RANKL-induced activation of NF- κ B and Jun N-terminal kinase (JNK) signaling pathways in BMMs [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] increases bone mineral density (BMD) content by improving the level of OPG and reducing the level of RANKL in ovariectomy-induced mice. Drynariae Rhizoma enhances the strength and hardness of bone [ 22 ]. Meanwhile, our previous studies reported that Drynaria flavonoids improve osteoporosis by promoting the expression of OPG and inhibiting RANKL and RANK in the sera of osteoporosis model rats [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported that polysaccharides from Rhizoma Drynariae exerts an antiosteoporotic effect in ovariectomized rats. It maintained trabecular microarchitecture and bone biomechanical properties, and increased femoral and tibial bone mineral density (BMD) [ 144 ].…”
Section: Other Botanicalsmentioning
confidence: 99%